Pitting corrosion resistant martensitic stainless steel and its manufacturing method
Patent Information
- Application Number
- JP2023555430
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-09
- Filing Date
- 2022-03-03
- Publication Date
- 2025-03-03
AI Technical Summary
Current martensitic stainless steels used in turbine airfoils are susceptible to pitting corrosion, particularly in harsh marine and industrial environments, leading to reduced mechanical properties and unscheduled downtime.
A forged martensitic stainless steel alloy with specific compositions and heat treatment processes, including cryogenic cooling, is developed to minimize retained austenite and intermetallic phases, enhancing pitting resistance and maintaining mechanical strength.
The alloy exhibits improved pitting corrosion resistance, maintaining high strength and toughness, reducing maintenance costs, and avoiding the need for additional coatings, suitable for turbine airfoils in harsh environments.
Smart Images

Figure 00000012_0000
Abstract
Description
[Technical field]
[0001] The invention disclosed herein relates generally to corrosion resistant stainless steels, and more particularly to pitting corrosion resistant martensitic stainless steels, including those suitable for rotating turbine components. [Background technology]
[0002] Metal alloys used in gas turbine rotating components, particularly pre-compressor airfoils, including rotor blades and stator vanes, must have a combination of high strength, toughness, fatigue resistance, and other physical and mechanical properties to provide the required operating characteristics for these machines. Additionally, the alloys used must be sufficiently resistant to various forms of corrosion and corrosion mechanisms, particularly pitting, due to the extreme operating environment of the turbine, including exposure to a variety of ionic reactive species, such as chlorides, sulfates, nitrides, and other corrosive species. Corrosion can degrade other required physical and mechanical properties, such as high cycle fatigue strength, by initiation of surface cracks that propagate under the cyclical heat and stresses associated with turbine operation.
[0003] Currently, there are no high strength steels that are sufficiently pitting resistant to withstand more than 2-3 years in harsh marine / industrial environments such as coastal industrial power plants. Even alloys known to have many advantageous corrosion resistance properties, including resistance to intergranular attack, such as 450 and 450+ stainless steels, are still susceptible to pitting mechanisms. Although these martensitic stainless steels have provided a combination of corrosion resistance, mechanical strength and fracture toughness properties suitable for use in steam and gas turbine rotating components, these alloys are still known to be susceptible to pitting corrosion phenomena. For example, stainless steel airfoils, such as those used in the pre-compressors of industrial gas turbines, have been found to be susceptible to pitting corrosion at the airfoil surfaces, particularly the leading edge surfaces. Without wishing to be bound by theory, it is believed that pitting corrosion is related to various electrochemical reaction processes activated by airborne deposits on the airfoil surface, particularly corrosive species present in the deposits and moisture from the intake air. Electrochemically initiated pitting corrosion phenomena at the airfoil surface can result in cracking of the airfoil due to the cyclic thermal and operating stresses to which these components are subjected. High levels of moisture can come from a variety of sources, such as use in high moisture environments, such as facilities located near oceans or other bodies of water, as well as online water washing, fogging, evaporative cooling, or various combinations thereof to increase compressor efficiency. Corrosive contaminants are common in the turbine operating environment, as turbines are often located in highly corrosive environments, such as near chemical and petrochemical plants where various chemical species may be present in the intake air, coastlines or other salt water environments where various sea salts may be present in the intake air, or combinations thereof, or other applications where the inlet air contains corrosive chemical species.
[0004] In view of the foregoing, stainless steel alloys suitable for use as turbine airfoils, particularly industrial gas turbine airfoils, in the above-mentioned operating environments and which have improved resistance to pitting corrosion would be highly desirable. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] US Patent Application Publication No. 2009 / 081068 Summary of the Invention
[0006] In one aspect, a method for producing a forged martensitic stainless steel alloy is provided. The method includes providing a forged preform of a martensitic pitting corrosion resistant stainless steel alloy comprising about 12.0% to about 16.0% by weight chromium, greater than 16.0% to about 20.0% by weight cobalt, about 6.0% to about 8.0% by weight molybdenum, about 1.0% to about 3.0% by weight nickel, about 0.020% to about 0.040% by weight carbon, the balance being iron and unavoidable impurities. The alloy has a microstructure comprising less than or equal to 2% retained austenite phase by volume of the microstructure. In a heating step, the forged preform is heated to a solution temperature for a time sufficient to form a solution microstructure. A cooling step cools the forged preform and solution microstructure to room temperature in a liquid, and then a soaking step soaks the forged preform in a cryogenic liquid to transform the retained austenite phase in the microstructure to martensite. A heating step heats the forged preform to a tempering temperature of less than 600° F. for a tempering time sufficient to form a tempered forged preform containing a tempered martensite microstructure. A cooling step cools the tempered forged preform to room temperature.
[0007] In another aspect, a method for making a forged martensitic stainless steel alloy is provided. The method includes providing a forged preform of a martensitic pitting corrosion resistant stainless steel alloy comprising about 12.0% to about 16.0% by weight chromium, greater than 16.0% to about 20.0% by weight cobalt, about 6.0% to about 8.0% by weight molybdenum, about 1.0% to about 3.0% by weight nickel, about 0.020% to about 0.040% by weight carbon, the balance being iron and unavoidable impurities. The alloy has a microstructure comprising no more than 2% by volume of the microstructure of retained austenite phase. In a heating step, the forged preform is heated to a solution temperature for a time sufficient to form a solutionized microstructure. In a cooling step, the forged preform and the solutionized microstructure are cooled to room temperature with a liquid, the liquid being an oil. The forged preform is immersed in oil and then, in a immersion step, the forged preform is immersed in a cryogenic liquid to transform the retained austenite phase in the microstructure to martensite. The cryogenic liquid is liquid nitrogen or liquid helium and has a temperature below -300° F. In a second heating step, the forged preform is heated to a tempering temperature below 600° F. for a tempering time sufficient to form a tempered forged preform containing a tempered martensite microstructure. In a second cooling step, the tempered forged preform is cooled to room temperature.
[0008] In yet another embodiment, the wrought martensitic stainless steel alloy comprises about 12.0 wt.% to about 16.0 wt.% chromium, greater than 16.0 wt.% to about 20.0 wt.% cobalt, about 6.0 wt.% to about 8.0 wt.% molybdenum, about 1.0 wt.% to about 3.0 wt.% nickel, about 0.020 wt.% to about 0.040 wt.% carbon, the balance being iron and unavoidable impurities. The alloy has a microstructure containing no more than 2 volume percent of the microstructure of retained austenite phase. The alloy has a microstructure that is substantially free of sigma (σ) phase. The alloy has a microstructure that is substantially free of Laves phase, chi (χ) phase, and delta (δ) ferrite phase. The alloy may be a turbine airfoil preform or a compressor airfoil preform.
[0009] In another embodiment, a wrought martensitic stainless steel alloy comprises about 12.0% to about 16.0% by weight chromium, greater than 16.0% to about 20.0% by weight cobalt, about 6.0% to about 8.0% by weight molybdenum, about 1.0% to about 3.0% by weight nickel, about 0.020% to about 0.040% by weight carbon, the balance being iron and incidental impurities. The alloy has a microstructure substantially free of sigma phase.
[0010] These and other advantages and features will become apparent from the following detailed description taken in conjunction with the accompanying drawings. [Brief description of the drawings]
[0011] The subject matter which is regarded as the invention is particularly and distinctly set forth in the claims at the end of this specification. These and other features and advantages of the embodiments described herein will become apparent from the following detailed description taken in conjunction with the accompanying drawings. [Figure 1] 1 is a flowchart of one embodiment of a method for producing a martensitic stainless steel alloy disclosed in the present application.
[0012] In the following detailed description, various embodiments, together with advantages and features, are described by way of example with reference to the drawings. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Such pitting is currently observed in in-service front compressor airfoils. The pitting resistant martensitic stainless steel alloys and methods described herein provide a corrosion and pitting resistant iron-base material that is a significant improvement for many heavy marine and industrial applications susceptible to such pitting phenomena, including front turbine compressor airfoils, in terms of service reliability, reduced maintenance concerns and costs, and avoidance of unscheduled downtime due to airfoil failure. The stainless steel alloys described herein are more pitting resistant than GTD-450 and GTD-450+ stainless steels, among others. Due to the significant operational costs associated with industrial gas turbine downtime, including the cost of purchased power to replace turbine power output, and the maintenance costs of dismantling the turbine to repair or replace the airfoils, as well as the costs of repairing or replacing the airfoils themselves, improved pitting resistance of alloys and methods of their manufacture are of great commercial value. An additional advantage of the pitting resistant iron-base alloys and methods of their manufacture is that no separate coatings need to be added for pitting protection. The stainless steel alloys described herein are specifically configured and well suited for forging, particularly for forging turbine airfoil components.
[0014] In an exemplary embodiment, the forged martensitic stainless steel alloy includes about 12.0% to about 16.0% by weight chromium, greater than 16.0% to about 20.0% by weight cobalt, about 6.0% to about 8.0% by weight molybdenum, about 1.0% to about 3.0% by weight nickel, about 0.020% to about 0.040% by weight carbon, the balance being iron and unavoidable impurities. More specifically, the forged martensitic stainless steel alloy includes about 13.5% to about 14.5% by weight chromium, greater than 16.0% to about 20.0% by weight cobalt, about 6.0% to about 6.5% by weight molybdenum, about 1.0% to about 3.0% by weight nickel, about 0.020% to about 0.30% by weight carbon, the balance being iron and unavoidable impurities. More specifically, the wrought martensitic stainless steel alloy comprises about 14 wt.% chromium, greater than 16.0 wt.% to about 20.0 wt.% cobalt, about 6.0 wt.% molybdenum, about 1.0 wt.% to about 3.0 wt.% nickel, about 0.025 wt.% carbon, the balance iron and incidental impurities. The stainless steel alloy composition is selected and configured to provide a martensitic microstructure upon heat treatment as described herein. The stainless steel alloy composition is selected and configured to provide a martensitic stainless steel alloy having a minimum tensile strength of about 150 ksi, a molybdenum content of greater than 6%, and a pitting resistance equivalent number (PREN) of greater than about 31.8. The stainless steel alloy disclosed herein achieves these corrosion and strength properties through a combination of composition chemistry and heat treatment. For example, the stainless steel alloys disclosed herein exhibit excellent resistance to pitting corrosion and may be heat treated to provide high strength and fracture toughness suitable for use as early stage turbine compressor airfoils (e.g., stages 1-5), including blades and vanes for industrial gas turbines. In another aspect, the stainless steel alloys described herein derive their strength primarily from solid solution strengthening associated with the development of a martensitic microstructure and martensitic reactions, while simultaneously reducing or minimizing the amount of retained austenite and containing substantially no delta ferrite, and in some embodiments, no delta ferrite at all.Large amounts of retained austenite (eg, greater than 2%) have been shown to be detrimental to corrosion resistance, and an upper limit of 2% (ie, less than or equal to 2% retained austenite) is preferred.
[0015] The Pitting Index provides a guide to comparing the pitting corrosion resistance (PREN) of stainless steel alloys based on alloy chemistry. The higher the PREN, the more resistant it is to pitting corrosion, but there is a practical limit as to how high the value can be increased before compromising the ability to properly heat treat the alloy. PREN can be calculated using Equation 1 below: PREN=(%Cr)+3.3(%Mo)+16(%N) (1) The martensitic stainless steel alloys described herein have a PREN greater than about 31.8, and more particularly greater than about 33.3. In one embodiment, the PREN is greater than about 31.8 to about 42.4, and more particularly from about 33.3 to about 36.0.
[0016] The stainless steel alloys disclosed herein can be described as iron-base alloys containing five alloying elements, including Cr, Mo, Co, Ni, and C. All other elements are impurities incidental to the manufacture of stainless steel and may include, by weight percent, for example, Mn (up to 0.25), Al (up to 0.03), V (up to 0.10), Si (up to 0.25), S (up to 0.005), or P (up to 0.02), and are kept below the maximum specified levels described herein to ensure lot-to-lot property and microstructural consistency. When balanced within the above ranges, the disclosed stainless steel alloys provide a martensitic microstructure with desirable strength and fracture toughness levels combined with pitting corrosion resistance.
[0017] As noted above, Cr is an essential element and is present in an amount sufficient to form a chromium oxide passivation film on the alloy surface. In one embodiment, Cr is present in an amount of about 11.5 wt% or greater. In another embodiment, Cr is present in an amount of about 12 to about 16 wt%, more specifically about 13.5 to about 14.5 wt%, and even more specifically about 14 wt%.
[0018] As shown in Equation 1, Mo (molybdenum) has a greater effect on the pitting corrosion resistance of stainless steels than Cr. In one embodiment, Mo is present in an amount of about 6.0 to about 8.0 wt%, more specifically about 6.0 to about 6.5 wt%, and even more specifically about 6 wt%. At least about 6 wt% is required to ensure sufficient resistance to pitting corrosion in marine chloride environments. Research has shown that Mo enhances the repassivation ability of stainless steels. Conventional high Mo content stainless steels are typically either ferritic grades or austenitic grades with high Ni (nickel) levels. The martensitic high Mo content stainless steel grades discussed herein are generally designed and heat treated at high tempering temperatures, such as 1100°F, for use at high operating temperatures, focusing on exploiting the ultra-high strength capabilities present in high temperature tempered materials. However, at high tempering temperatures, these materials sacrifice corrosion resistance and toughness due to the depletion of the corrosion-resistant Mo and Cr matrix by the precipitation and formation of Mo-rich and Cr-rich intermetallic phases. At high tempering temperatures, the formation of these intermetallic compounds also produces a secondary hardening effect. These intermetallic phases include Laves phase (Fe2Mo), Fe7Mo6, FeMo, sigma phase (Fe-Cr-Mo) and complex BCC chi phase (Fe-Cr-Mo). Sigma phases can form during quenching and tempering and are undesirable minor elements. Cobalt does not participate in these precipitation reaction-related phases. These intermetallic phases also dramatically reduce the toughness of the alloy. Therefore, the martensitic stainless alloys described herein are tempered at low tempering temperatures as described herein to avoid the precipitation of these intermetallic phases. The tempered alloys are suitable for use in relatively low temperature applications where corrosion resistance with moderate strength and good toughness is important. The martensitic stainless alloys described herein combine high Mo additions with the low tempering temperature region of the hardness versus tempering temperature curve to avoid the formation of intermetallic phases and keep Mo and Cr in solid solution to maintain high levels of toughness.In one embodiment, the microstructure of the martensitic stainless steel alloy is substantially free of Laves phase, and in some embodiments, is completely free of Laves phase. In another embodiment, the microstructure of the martensitic stainless steel alloy is substantially free of Chi phase, and in some embodiments, is completely free of Chi phase. In yet another embodiment, the microstructure of the martensitic stainless steel alloy is substantially free of Delta ferrite phase, and in some embodiments, is completely free of Delta ferrite phase. In another embodiment, the microstructure of the martensitic stainless steel alloy is substantially free of Sigma phase, and in some embodiments, is completely free of Sigma phase. In yet another embodiment, the microstructure of the martensitic stainless steel alloy is substantially free of Laves, Chi, Delta ferrite, and Sigma phases, and in some embodiments, is completely free of Laves, Chi, Delta ferrite, and Sigma phases.
[0019] As can be seen from formula 1, N has a large effect on PREN and may be suitably included in the claimed stainless steel material. However, N is difficult to add in large quantities to vacuum melted materials. Furthermore, N may combine with Cr in the alloy microstructure to form chromium nitrides, which may embrittle and sensitize the stainless steel material due to localized depletion of chromium in the microstructure, especially at the alloy surface that may come into contact with corrosive chemical species. Thus, when present, N is generally present in an amount of 0.02 wt.% or less, more specifically about 0.001 to about 0.02 wt.%.
[0020] A high temperature austenite microstructure is required to develop a martensite microstructure from the martensitic transformation. Thus, the claimed stainless steel alloy composition will have a high temperature microstructure that includes austenite. Since Cr and Mo are both ferrite stabilizers, an austenite former is required to balance the phase diagram and develop a high temperature austenite phase to facilitate martensite heat treatment to provide a martensite microstructure while at the same time developing a predetermined maximum amount of retained austenite and being substantially free of delta ferrite, in some embodiments without any delta ferrite. Retained austenite is undesirable in this alloy and should be kept below a maximum of 2%. Co is selected to stabilize austenite. In one embodiment, Co is present in an amount of about 16.0 to about 20.0 wt%, more specifically about 16.5 to about 20.0 wt%, and even more specifically about 16.5 to about 18.0 wt%. As an austenite stabilizer, cobalt provides a sufficiently large austenite phase range for the temperature and / or time tolerances in heat treatment processes. S The effect of Co on the quenching and tempering temperature is not as pronounced as that of Ni. Standard quenching and tempering protocols are not sufficient for the alloys described herein. Cryogenic treatment in a cryogenic liquid (such as liquid nitrogen or liquid helium) to temperatures below -300°F is required to transform the austenite remaining after a conventional quenching operation to martensite. This cryogenic operation occurs between the quenching and tempering processes.
[0021] Ni is an essential element and is present in an amount sufficient to stabilize austenite. Ni is an austenite stabilizer and increases the amount of retained austenite in these alloys. Thus, the amount of Ni should be controlled to provide a predetermined maximum amount of retained austenite phase in the alloy microstructure. In one embodiment, the predetermined maximum amount of retained austenite phase comprises 2% or less by volume (i.e., 0-2% by volume) of the alloy microstructure. In other embodiments, the predetermined amount of retained austenite phase comprises about 0-1.5% by volume, 0.5-2% by volume, or 0.5-1.5% by volume of the alloy microstructure. In one embodiment, the amount of Ni is about 1.0 to about 3.0% by weight, more specifically, about 1.0 to about 2.0% by weight, and even more specifically, about 1.0 to about 1.5% by weight. The predetermined maximum amount of retained austenite improves the fracture toughness of the claimed alloys. Ni is M S The temperature is significantly reduced, and the amounts disclosed herein are consistent with the heat treatment temperatures and times disclosed herein. S The Ni content provides a desired temperature and provides a desired martensite structure while promoting a desired amount of retained austenite. The amount of Ni described herein also increases the Charpy V-notch toughness of the martensitic stainless steel alloy described herein. Ni is added to promote austenite formation during austenitization and minimize the formation of delta ferrite. In the present alloy, the presence of excessive retained austenite is undesirable since it makes the microstructure more susceptible to corrosion attack. The presence of austenite in the microstructure forms galvanic couples with adjacent martensite, leading to accelerated attack in corrosive aqueous media. The retained or untransformed austenite forms galvanic couples with adjacent martensite. Therefore, the retained austenite content should be kept below a maximum of 2 volume percent of the alloy microstructure to ensure best pitting corrosion resistance.
[0022] As mentioned above, C (carbon) is an essential component and is present in an amount sufficient to provide a desired hardness and / or a desired tensile strength. The amount of C is also determined by the coarse M 23The amount of C is selected to avoid the formation of C6 carbides. These carbides preferentially nucleate at grain boundaries, reducing toughness. Chromium carbides also deplete the matrix around the chromium carbides, reducing corrosion resistance. In one embodiment, C is present in an amount less than about 0.05 wt.%. In another embodiment, C is present in an amount of about 0.020 to about 0.040 wt.%, more specifically about 0.20 to about 0.030 wt.%, and even more specifically about 0.025 wt.%. In one embodiment, the predetermined hardness is about 30 to about 42 HRC, and the predetermined ultimate tensile strength (UTS) is about 150 to about 200 ksi. The amount of C can be used in conjunction with a low temperature tempering heat treatment as described herein to provide a predetermined strength and a predetermined fracture toughness sufficient for use as turbine airfoil components (e.g., turbine compressor vanes and blades, more specifically turbine compressor vanes and blades suitable for use in the first to fifth stages of industrial gas turbine compressors).
[0023] Referring to FIG. 1, according to another embodiment, a method 100 for producing a wrought martensitic corrosion resistant stainless steel alloy is disclosed. The method 100 includes a step 110 of preparing a wrought preform of a martensitic corrosion resistant stainless steel alloy comprising about 12.0% to about 16.0% by weight chromium, greater than 16.0% to about 20.0% by weight cobalt, about 6.0% to about 8.0% by weight molybdenum, about 1.0% to about 3.0% by weight nickel, about 0.020% to about 0.040% by weight carbon, the balance being iron and unavoidable impurities. The stainless steel alloy may be prepared by any suitable method, including substantially conventional processing. For example, the alloy may be produced by electric furnace melting with argon oxygen decarburization (AOD) ladle refining followed by electroslag remelting (ESR) of the ingot. Other similar melting methods may also be used. The bar may then be produced using an appropriate forming operation, such as various forging methods, to produce a forged preform having a precursor shape for a desired article, including various articles described herein, such as turbine compressor airfoils.
[0024] The method 100 also includes heating 120 the forged preform to a solution temperature for a time sufficient to form a solution microstructure. In one embodiment, the solution temperature is from about 2000° F. to about 2100° F., and the solution time is from about 1 hour to about 3 hours.
[0025] The method further includes step 130 of cooling the forged preform and solutionized microstructure to room temperature to form a martensitic microstructure. Any suitable cooling method that provides a cooling rate sufficient to promote the martensitic transformation of the alloy microstructure may be used. In one embodiment, the cooling includes a water, polymer, or oil quench. Gas or air quenching is insufficient to prevent the formation of sigma phase upon cooling. More specifically, a cooling rate of 0.25° C. / sec is required to inhibit sigma phase formation in high alloy stainless steels.
[0026] The method further includes immersing 140 the forged preform 140 in a cryogenic liquid at a temperature below -300°F. The cryogenic cooling transforms the retained austenite phase into martensite. The cryogenic treatment is performed in a cryogenic liquid (such as liquid nitrogen or liquid helium) to a temperature below -300°F and is required to transform the retained austenite into martensite after the conventional quenching operation. This cryogenic operation occurs between the quench / cool 130 and temper / heat 150 process steps.
[0027] The method also includes heating 150 the forged preform to a tempering temperature of less than about 600°F for a predetermined tempering time sufficient to form a tempered forged preform comprising a tempered martensite microstructure. Any suitable heating method and tempering time may be used. In one embodiment, the predetermined tempering time is from about 3 hours to about 6 hours. In one embodiment, the tempered forged preform comprises a turbine airfoil preform or a compressor airfoil preform. A low tempering temperature of less than 600°F is used to avoid the formation of the precipitates described herein, particularly the embrittling chi, Laves and sigma phases. It has been found that the presence of more than 3.5% Mo in 12% Cr steels leads to high temperature aging reactions based on the precipitation of Laves phases. High Mo content can result in high temperature formation of intermetallic chi and sigma phases, which increase brittleness and reduce tensile ductility. The formation of these compounds results in a dramatic loss of impact resistance. Thus, the emphasis is on solid solution strengthening (both substitutional and interstitial carbon) and low temperature tempering at temperatures below 600°F. Low temperature tempering establishes a predetermined maximum operating temperature for these alloys, which is lower than the tempering temperature, and preferably at least about 50 to about 100°F below the tempering temperature to avoid subsequent martensite tempering and changes to the alloy microstructure. It is desirable to keep as much of Cr and Mo in solid solution as possible, both to provide corrosion resistance and to keep these elements from bonding to intermetallics or carbides. The formation of sigma phases during quenching or tempering is problematic. The formation of sigma phases is detrimental to corrosion resistance and toughness. Tempering temperatures are kept below 600°F to prevent the formation of sigma, chi, and Laves phases, which embrittle the alloy and reduce pitting resistance.
[0028] In addition to being pitting resistant, the martensitic stainless steel alloys disclosed herein have a combination of strength, ductility, and fracture toughness that make them suitable for use in forming a variety of turbine airfoils, blades, and other components. In one embodiment, the martensitic stainless steel alloy exhibits superior pitting resistance to GTD-450 and GTD-450+ after 500 hours of salt spray according to ASTM G85, and in another embodiment, exhibits substantially no pitting after 500 hours of salt spray according to ASTM G85, which may in some embodiments be described as no pitting at all for this salt spray experiment. In another embodiment, the martensitic stainless steel alloys disclosed herein exhibit substantially no pitting after 1000 hours of salt spray according to ASTM B117, which may in some embodiments be described as no pitting at all for this salt spray experiment. In one embodiment, the martensitic stainless steel alloy has an ultimate tensile strength of at least about 150 ksi, and more specifically, from about 150 to about 200 ksi. In another embodiment, the martensitic stainless steel alloy has a room temperature elongation of about 11%. In yet another embodiment, the martensitic stainless steel alloy has a tensile reduction in area of about 39%. In yet another embodiment, the martensitic stainless steel alloy has a Charpy V-notch impact toughness of about 20 J (16 ft-lbs).
[0029] The alloys and methods disclosed herein may be used to form turbine airfoil components, including those used in compressor airfoil components of industrial gas turbines. Typical compressor airfoils in the form of turbine compressor blades are well known. Compressor blades have a leading edge, a trailing edge, a tip, and a blade root (such as a dovetail root suitable for removable attachment to a compressor disk). The span of the blade extends from the tip to the blade root. The surface of the blade contained within the span constitutes the airfoil surface of the turbine airfoil. The airfoil surface is that portion of the turbine compressor airfoil exposed to the flow path of air flowing from the turbine inlet through the compressor section of the turbine to the turbine combustion chamber and other portions of the turbine. The alloys and methods disclosed herein are particularly useful for use in turbine compressor airfoils in the form of turbine compressor blades and vanes, but are generally applicable to all types of turbine compressor airfoils used in a wide variety of components. Such components include turbine airfoils associated with turbine compressor vanes and nozzles, shrouds, liners and other turbine compressor airfoils, i.e., turbine components having airfoil surfaces such as diaphragm components, seal components, valve stems, nozzle boxes, nozzle plates, etc. Also, while these alloys and methods are useful for gas turbine compressor blades and vanes, they can potentially be used in turbine components for industrial steam turbines (e.g., compressor blades and vanes, steam turbine buckets and other steam turbine airfoil components), oil and gas machine components, and other applications requiring high tensile strength, fracture toughness and pitting corrosion resistance, so long as the operating temperature range of the component is compatible with the specified maximum use temperatures of the alloys described herein.
[0030] As used herein, the indefinite article does not denote a limitation of quantity but rather means that there is one or more of the item to which the indefinite article is attached. The modifier "about" used in connection with a quantity is inclusive of the recited numerical value and has a meaning dictated by the context (e.g., including the degree of error associated with measurement of the particular quantity). Furthermore, unless otherwise limited, all ranges disclosed herein are inclusive and combinable (e.g., a range such as "up to about 25 wt. %, more specifically, 5 wt. % to about 20 wt. %, and even more specifically, about 10 wt. % to about 15 wt. %" includes the upper and lower limits of that range and all intermediate values (e.g., "about 5 wt. % to about 25 wt. %, about 5 wt. % to about 15 wt. %, etc.)). When used in connection with a list of ingredients of an alloy composition, "about" applies to all ingredients recited and, when used in connection with a range, applies to the upper and lower limits of that range. Finally, unless otherwise defined, as used herein, "about" applies to all ingredients recited and, when used in connection with a range, applies to the upper and lower limits of that range. Technical and scientific terms have the same meaning as commonly understood by one of ordinary skill in the art. Terms in parentheses with the plural suffix "s" indicate both the singular and plural inclusion of the term, including one or more of the term (e.g., "metal(s)" includes one or more metals). Throughout this specification, references such as "one embodiment," "another embodiment," "embodiment," and the like, mean that a particular component (e.g., a feature, structure, and / or characteristic) described with respect to that embodiment is included in one or more embodiments described herein, and may or may not be present in other embodiments.
[0031] The term "comprising" as used with respect to the alloy compositions described herein is intended to specifically disclose and include embodiments in which the alloy composition "consists essentially of" (i.e., contains the recited components and does not contain other components that substantially adversely affect the basic and novel characteristics disclosed) as well as embodiments in which the alloy composition "consists" (i.e., contains only the recited components, other than impurities that are naturally and unavoidably present in each of the recited components).
[0032] Although the present invention has been described in detail with respect to a limited number of embodiments, it should be apparent that the present invention is not limited to these disclosed embodiments. The present invention can be modified to introduce numerous changes, modifications, substitutions or equivalent arrangements that are consistent with the spirit and scope of the present invention, although not described herein. Moreover, while various embodiments have been described, aspects of the invention may include only some of the described embodiments. Thus, the present invention is not limited by the above description, but rather is limited only by the scope of the appended claims.
[0033] Other aspects of the present invention are set forth in the following embodiments. [Embodiment 1] 1. A method for producing a forged martensitic stainless steel alloy, comprising the steps of: preparing a forged preform of a martensitic pitting corrosion resistant stainless steel alloy comprising about 12.0% to about 16.0% by weight chromium, greater than 16.0% to about 20.0% by weight cobalt, about 6.0% to about 8.0% by weight molybdenum, about 1.0% to about 3.0% by weight nickel, about 0.020% to about 0.040% by weight carbon, the balance being iron and unavoidable impurities, wherein the alloy has a microstructure comprising about 15% or more by volume of retained austenite phase in the microstructure; and forging the forged preform. The method includes the steps of heating the preform to a solution temperature for a time sufficient to form a solution microstructure, cooling the forged preform and the solution microstructure to room temperature with a liquid, then immersing the forged preform in a cryogenic liquid to transform the retained austenite phase in the microstructure to martensite, heating the forged preform to a tempering temperature of less than 600°F for a tempering time sufficient to form a tempered forged preform comprising a tempered martensite microstructure, and cooling the tempered forged preform to room temperature. [Embodiment 2] 2. The method of embodiment 1, wherein the solutionizing temperature comprises about 2000 to about 2100° F. and the time comprises about 1 to about 3 hours. [Embodiment 3] 3. The method of any one of the preceding claims, wherein the liquid in the cooling step comprises oil or water, and the forged preform and the solutionized microstructure are immersed in the liquid. [Embodiment 4] 4. The method of any one of claims 1 to 3, wherein the cryogenic liquid in the immersion step comprises liquid nitrogen or liquid helium. [Embodiment 5] The method according to any one of the preceding claims, wherein the tempering time is from about 3 hours to about 6 hours. [Embodiment 6]
[0023] Embodiment 6. The method of any one of embodiments 1 to 5, wherein the tempered forged preform comprises a turbine airfoil preform or a compressor airfoil preform. [Embodiment 7] 7. The method of any one of the preceding claims, wherein the retained austenite phase comprises less than or equal to 2% by volume of the microstructure. [Embodiment 8] 2. The method of embodiment 1, wherein the alloy has a microstructure that is substantially free of Laves phase, Chi phase, or delta ferrite phase. [Embodiment 9] The method of any one of the preceding claims, wherein the alloy has a microstructure that is substantially free of sigma phase. [Embodiment 10] providing a forged preform of a forged martensitic pitting corrosion resistant stainless steel alloy comprising about 12.0% to about 16.0% by weight chromium, greater than 16.0% to about 20.0% by weight cobalt, about 6.0% to about 8.0% by weight molybdenum, about 1.0% to about 3.0% by weight nickel, about 0.020% to about 0.040% by weight carbon, the balance being iron and unavoidable impurities, the alloy having a microstructure containing no more than 2% by volume of the microstructure as retained austenite phase; and heating the forged preform to a solution temperature for a time sufficient to form a solution microstructure. cooling the forged preform and the solutionized microstructure to room temperature in a liquid, the liquid being oil, immersing the forged preform in the oil; then immersing the forged preform in a cryogenic liquid to transform retained austenite phase in the microstructure to martensite, the cryogenic liquid being liquid nitrogen or liquid helium and having a temperature below -300°F; heating the forged preform to a tempering temperature of less than 600°F for a tempering time sufficient to form a tempered forged preform comprising a tempered martensite microstructure; and cooling the tempered forged preform to room temperature. [Embodiment 11] 11. The method of embodiment 10, wherein the alloy has a microstructure that is substantially free of sigma phase. [Embodiment 12] A wrought martensitic stainless steel alloy comprising about 12.0% to about 16.0% by weight chromium, greater than 16.0% to about 20.0% by weight cobalt, about 6.0% to about 8.0% by weight molybdenum, about 1.0% to about 3.0% by weight nickel, about 0.020% to about 0.040% by weight carbon, the balance being iron and unavoidable impurities, wherein the alloy has a microstructure containing no more than 2% by volume of retained austenite phase in the microstructure. [Embodiment 13] 13. The alloy of embodiment 12, wherein the alloy has a microstructure that is substantially free of sigma phase. [Embodiment 14] 14. The alloy of embodiment 12 or embodiment 13, wherein the alloy has a microstructure that is substantially free of Laves phase, Chi phase, and delta ferrite phase. [Embodiment 15] 15. The alloy of any one of claims 12 to 14, wherein the alloy comprises a turbine airfoil preform or a compressor airfoil preform. [Embodiment 16] % chromium, greater than 16.0% to about 20.0% by weight cobalt, about 6.0% to about 8.0% by weight molybdenum, about 1.0% to about 3.0% by weight nickel, about 0.020% to about 0.040% by weight carbon, the balance being iron and unavoidable impurities, wherein the alloy has a microstructure that is substantially free of sigma phase. [Embodiment 17] 17. The alloy of any one of claims 10 to 16, wherein the alloy has a microstructure containing less than or equal to 2% by volume of the microstructure as retained austenite phase. [Embodiment 18] 18. The alloy of any one of embodiments 10 to 17, wherein the alloy has a microstructure that is substantially free of Laves phase, Chi phase, and delta ferrite phase. [Embodiment 19] 19. The alloy of any one of claims 10 to 18, wherein the alloy comprises a turbine airfoil preform or a compressor airfoil preform.
Claims
1. A method (100) for producing a wrought martensitic stainless steel alloy, comprising: 110, providing a forged preform of a martensitic, pitting corrosion resistant stainless steel alloy comprising about 12.0% to about 16.0% by weight chromium, greater than 16.0% to about 20.0% by weight cobalt, about 6.0% to about 8.0% by weight molybdenum, about 1.0% to about 3.0% by weight nickel, about 0.020% to about 0.040% by weight carbon, the balance iron and unavoidable impurities, said alloy having a microstructure containing 2% or less by volume of retained austenite phase in the microstructure; heating (120) the forged preform to a solution temperature of about 2000° F. (1093° C.) or greater for at least one hour, the time being sufficient to form a solution microstructure; cooling (130) the forged preform and solution microstructure to room temperature in a liquid; then immersing the forged preform in a cryogenic liquid at a temperature below −300° F. (−184° C.) (140) to transform the retained austenite phase in the microstructure to martensite; heating (150) the forged preform to a tempering temperature of less than 600° F. (315° C.) for a tempering time of at least 3 hours sufficient to form a tempered forged preform comprising a tempered martensite microstructure; Cooling the tempered forged preform to room temperature (160); The method includes:
2. 2. The method of claim 1, wherein the solutionizing temperature is from about 2000 to about 2100° F. (1093 to 1150° C.) and the time is from about 1 to about 3 hours.
3. 3. The method of claim 1 or claim 2, wherein the liquid in the cooling step (130) comprises oil or water, and the forged preform and solution microstructure are immersed in the liquid.
4. 4. The method of claim 1, wherein the cryogenic liquid in the immersion step (140) comprises liquid nitrogen or liquid helium.
5. The method of any one of claims 1 to 4, wherein the tempering time is from about 3 hours to about 6 hours.
6. The method of any one of claims 1 to 5, wherein the temper forged preform comprises a turbine airfoil preform or a compressor airfoil preform.
7. 7. The method of claim 1, wherein the alloy has a microstructure that is substantially free of Laves phase, Chi phase, or delta ferrite phase.
8. 8. The method of claim 1, wherein the alloy has a microstructure that is substantially free of sigma phase.
9. 1. A forged martensitic stainless steel alloy, comprising: about 12.0 wt.% to about 16.0 wt.% chromium; greater than 16.0 wt. % to about 20.0 wt. % cobalt; about 6.0% to about 8.0% by weight molybdenum; about 1.0 wt. % to about 3.0 wt. % nickel; about 0.020% to about 0.040% by weight carbon; An alloy having a microstructure containing no more than 2% by volume of the microstructure of retained austenite phase, the balance being iron and incidental impurities.
10. 10. The alloy of claim 9, wherein the alloy has a microstructure that is substantially free of sigma phase.
11. 11. The alloy of claim 9 or claim 10, wherein the alloy has a microstructure that is substantially free of Laves phase, Chi phase, and delta ferrite phase.
12. 12. The alloy of any one of claims 9 to 11, wherein the alloy comprises a turbine airfoil preform or a compressor airfoil preform.